Sticky Bacteria: Understanding the Behavior of a D-Galactose Adapted Consortium of Acidophilic Chemolithotroph Bacteria and Their Attachment on a Concentrate of Polymetallic Mineral - Aguirre, Paulina; Saavedra, Albert; Moncayo, Eduardo; Hedrich, Sabrina; Guerrero, Karlo; Gentina, Juan Carlos (Frontiers in Microbiology, 2021)
Various strategies to accelerate the formation of biofilms on minerals have been studied, one of them is the use of D-galactose as an inducer of EPS production in planktonic cells of biooxidant bacteria. With the aim to evaluate the influence on the attachment and the effect over the solubilization of a polymetallic mineral concentrate, the behavior of a microbial consortium formed by Acidithiobacillus thiooxidans DSM 14887T and Leptospirillum ferrooxidans DSM 2705T previously induced with D-galactose for the early formation of EPS was studied. These microorganisms were previously adapted to 0.15% and 0.25% of D-galactose respectively, afterwards, different proportions of both strains were put in contact with the particle surface of a concentrate of polymetallic mineral. Also, to evaluate the affinity of each bacterium to the mineral, attachment tests were carried out with one of this species acting as a pre-colonizer. The same consortia were used to evaluate the solubilization of the polymetallic mineral. The results obtained show that the induction by D-galactose increases the microbial attachment percentage to the mineral by at least 10% with respect to the control of non-adapted consortia. On the other hand, the tests carried out with pre-colonization show that the order of inoculation also affects the microbial attachment percentage. From the different proportions tested, it was determined that the use of a consortium with a proportion of 50% of each species previously adapted to D-galactose and inoculated simultaneously, present a microbial attachment percentage to the mineral greater than 95% and better solubilization of a polymetallic mineral, reaching values of 9.7 y 11.7 mg·L-1·h-1 of Fe3+ and SO42- respectively. Therefore, the use of D-galactose in small concentrations as inducer of EPS in acidophilic cells and the selection of an adequate strategy of inoculation can be beneficial to improve biooxidation since it would allow this process to develop in a shorter time by achieving a greater number of attached cells in a shorter time accelerating the solubilization of a sulfide mineral.